2019
DOI: 10.3139/120.111402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of notch-depth ratio on intermittent electromagnetic radiation from Cu-Ni alloy under tension

Abstract: This paper presents some experimental results on the effect of the notch–depth ratio on intermittent electromagnetic radiation during the progressive plastic deformation of a Cu-Ni alloy sheet specimen under tension. An electromagnetic antenna was used for receiving the electromagnetic waves emitted by the deforming specimen. The specimens (with varied notch-depth ratios) first emit electromagnetic radiation near yield which is always oscillatory in nature. However, the axial strain at the initial emission of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The failure occurs because of the influence of a stress-free boundary on the stress field surrounding the fracture tip. As a result, it is suggested that an ideal 2a/w range of 0.45 to 0.55 [19] is maintained.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The failure occurs because of the influence of a stress-free boundary on the stress field surrounding the fracture tip. As a result, it is suggested that an ideal 2a/w range of 0.45 to 0.55 [19] is maintained.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 shows the stress-strain plot depicting the stages of intermittent EMR emission for 2a/w = 0.33. The EMR signal for various metallic materials [13][14][15][16][17][18][19] exhibits exponential decaying and damped oscillating characteristics. Figure 4a shows the first EMR emission signal near yielding for 2a/w = 0.33, indicating an oscillating damping nature.…”
Section: Influence Of 2a/w On Emr Signal Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that the changes in the ratio change the nature of EMR, i.e. from oscillatory to exponential, and have also helped to develop the correlation between the EMR emission parameters and the radius of the plastic zone [184]. Recently Oraon and Sharma presented an experimental investigation to determine EMR radiation during incremental microforming of a thin aluminium sheet.…”
Section: Electromagnetic Effects In Metals and Alloysmentioning
confidence: 99%